Efek Pemberian Buah Biksu (Siraitia grosvenorii) dalam Pakan terhadap Karakteristik Fisik dan Kimia Daging Ayam Broiler: Effect of Monk Fruit (Siraitia grosvenorii) Supplementation in Feed on the Physicochemical Characteristics of Broiler Chicken Meat - Aryanti Candra Dewi; Utami, Merry Muspita Dyah; Hertamawati, Rosa Tri (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The research aimed to determine the effect of monk fruit (Siraitia grosvenorii) in the ration on the physicochemical quality of broiler chicken meat. A total of two hundred DOC broilers were distributed using a completely randomized design into five treatments and four replications, each replication containing 10 birds. Feeding treatment was carried out starting from 7-day-old chickens, consisting of treatments without monk fruit supplementation (T0), 0.5% monk fruit flour supplementation (T1), 1% monk fruit flour supplementation (T2), 1.5% monk fruit flour supplementation (T3), and 2% monk fruit flour supplementation (T4). The mixed ration consisted of corn, rice bran, palm oil, broiler concentrate, top mix, calcium carbonate, monk fruit meal, and fish meal. Broiler chickens were slaughtered at the age of 36 days, and samples of thigh and breast meat were taken to observe chemical quality (pH and water content), as well as physical quality (water holding capacity, cooking loss, and hardness). Data were analysed using Analysis of Variance followed by Duncan Multiple Range Test. The results showed that the supplementation of monk fruit had a significant effect (p<0.05) on pH, water content, water holding capacity, cooking loss, and hardness of thigh and breast meat. The conclusion of this study was that supplementation of monk fruit increased the pH and moisture content of the thigh meat, as well as increased the water-holding capacity, hardness, and reduced the cooking loss of both thigh and breast meat. Keywords:           breast meat, broiler meat quality, monk fruit, thigh meat